Disputes Over Frozen Preembryos & the “Right Not to Be a Parent” - Pachman, Tracey S. (Columbia Journal of Gender and Law, 2003)
In the past few decades, medical science has progressed at a breakneck pace to provide solutions that allow infertile couples to conceive and gestate their own biological children. Not surprisingly, the speed of these medical developments, which have altered the character of human reproduction, has left the U.S. legal system scrambling to create legal standards with respect to individual rights. An excellent example of this phenomenon occurs in the context of in vitro fertilization [hereinafter IVF], where several courts have developed guidelines to resolve frozen preembryo disputes. When these courts apply long-standing legal principles to the unique circumstances of disputes over control of frozen preembryos [hereinafter “preembryo dispute cases”], it may look like jurisprudence as usual. Yet, this line of cases demands intense scrutiny, particularly from feminist scholars. The holdings of the preembryo dispute cases are molding reproductive rights in our legal system to accommodate new understandings of reproduction. Unfortunately, the shape that these rights are taking does not wear well on women. In order to understand how cases involving the reproductive innovation of IVF are directing the course of reproductive rights in the United States and impacting women, it is important to first understand the IVF process and how it generates disputes. This article explores the “right not to be a parent,” the controlling standard by which several courts have decided disputes over frozen preembryos. In Part II, I describe both the IVF process and how courts have responded to disputes that have arisen from it. Part III of this article reveals that the “right not to be a parent” has weak, if any, footing in constitutional and family law. Part IV of this paper demonstrates that although it appears to be gender-neutral, the application of the right not to be a parent in preembryo dispute cases effectively discriminates against women by failing to recognize contributions and rights of women in the lVF procedure. Furthermore, this Part discusses how the arbitrary decision to focus on the future benefits and burdens of parenthood, rather than the past contributions to the couples’ efforts to achieve parenthood, devalues the enormous contributions of women to the lVF procedure and thereby discriminates against women in preembryo disputes. Finally, I propose a new standard that combines freedom to contract with acknowledgment of women’s more significant role in the IVF process, to allow resolution of preembryo dispute cases in a manner that preserves women’s personal and reproductive rights.